Skin and mucosal manifestations of cancer treatments in Lomé (Togo): A series of 35 cases - Abla Sefako Akakpo; Ahoefa Oyenitiniwa Ablavi Adani-Ifè; Téclessou Julienne Noude; Panawe Kassang; Abas Mouhari-Toure; Koussake Kombaté; Bayaki Saka; Palokinam Pitché (Our Dermatology Online, 2022)
Objective: This study aimed to describe the mucocutaneous manifestations of anti-cancer treatments in cancer patients in Lomé (Togo). Patients and Method: This is a descriptive cross-sectional study conducted in the oncology department of the Sylvanus Olympio University Hospital and in a private medical clinic in Lomé over 6 months. Results: A total of 35 patients were included with 26 patients (74.3%) receiving either mono or multidrug therapy or 9 (25.7%) receiving radiotherapy. The mean age of the patients was 52±11.36 years with extremes ranging from 24 to 71 years and the sex ratio (M/F) was 0.35. The main drugs used during chemotherapy were platinum salts (n=18; 69.2%), antimetabolites (n=15; 61.5%), taxanes (n=9; 34.6), topoisomerase inhibitors (n=7; 26.9%), alkylating agents (n=6; 23.1%). The main mucocutaneous manifestations observed were localized hyperpigmentation (palms and soles, fingertips, tongue) noted in 11 patients (n=42.3%), followed by alopecia observed from the first treatment (n=8; 30.8%), skin xerosis (n=4; 15.4%), and oral involvement (aphthoid lesions, gingivitis), (n=4; 15.4%). Radiodermatitis grade 3, 2 and 1 was noted in 4 patients (44; 4%), 4 other patients (44.4%) and 1 patient (11.2%) respectively. Conclusion: Our study identifies localized hyperpigmentation, alopecia, grade 3 and 2 radiodermatitis as the respective mucocutaneous manifestations of multidrug therapy and radiotherapy in Lomé, Togo.